Generation of CD1 tetramers as a tool to monitor glycolipid-specific T cells. - Gadola, S; Karadimitris, A; Zaccai, N; Salio, M; Dulphy, N; Shepherd, D; Jones, E; Cerundolo, V (2003)
CD1 molecules are beta(2)m-associated HLA class-I-like glycoproteins which have the unique ability to present glycolipid and phospholipid antigens to specific T lymphocytes. To study the biology of CD1 and its role in human disease we developed novel techniques for generation of recombinant CD1/lipid complexes by in vitro refolding. Fluorescent tetrameric complexes made from soluble recombinant CD1d/alpha-galactosylceramide complexes allowed highly sensitive and specific ex vivo and in vitro detection and functional characterization of novel human T-lymphocyte populations. Furthermore, protein crystals were obtained from soluble recombinant CD1b/beta(2)m-proteins loaded either with phosphatidylinositol or ganglioside GM2, which led to the first atomic structure determination of a CD1/lipid complex. The analysis of these crystal structures clarified how CD1b molecules can bind lipid ligands of different size, and revealed a broader spectrum of potential CD1b ligands than previously predicted.